Nearly Complete Response of Brain Metastases from HER2 Overexpressing Breast Cancer with Lapatinib and Capecitabine after Whole Brain Irradiation - Esin Oktay; Özlem Yersal; Nezih Meydan; Mehmet Sağıroğlu; Ömer Uyanık; Sabri Barutca (Case Reports in Oncological Medicine)
Trastuzumab treatment does not prevent intracranial seeding and is largely ineffective for established central nervous system metastasis in HER2 overexpressing breast cancer patients. Combination therapy of lapatinib and capecitabine may be an effective treatment option for brain metastasis of HER2-positive breast cancer. We report a patient with breast cancer overexpressing HER-2 where brain metastases were successfully treated with radiation and a combination of lapatinib and capecitabine.